Pemberdayaan Industri Rumahan Dusun Tungu Desa Kayangan Kecamatan Diwek Kabupaten Jombang - Rofiatin, Umi Rofiatin; Pudjiastuti, Agnes Quartina; Suhudi, Suhudi (JAST : Jurnal Aplikasi Sains dan Teknologi, 2023)
Home-scale food processing industries (small businesses) often experience various obstacles in developing their businesses. Generally, they have small capital, the business location is still one with activities in the house, and the marketing area is very limited (local in nature). These characteristics and problems were also found in the home industry of making purple sweet potato onde-onde owned by one of the residents in Kayangan Village, Diwek District, Jombang Regency. The objectives of this activity are 1) increasing production through assistance in the form of mixers and production process equipment, 2) improving business management through counseling/training on simple bookkeeping, cost and income analysis, and 3) expanding marketing areas through counseling/training on online marketing. Activities carried out by partners are 1) assisting with mixer equipment, along with counseling/training about its operation and maintenance, 2) counseling/training about simple bookkeeping and cost and income analysis, so that partners can find out business profits/losses, 3) counseling/training about marketing communication techniques and online marketing via WhatsApp, Facebook, Instagram. The output achieved is an increase in production by 46% and income by 45.8% as well as partner skills.ABSTRAKIndustri rumahan olahan pangan yang berskala rumahtangga (usaha kecil) sering mengalami berbagai kendala dalam mengembangkan usahanya. Umumnya mereka memiliki modal yang kecil, tempat usaha masih menjadi satu dengan aktivitas dalam rumah, wilayah pemasaran sangat terbatas (bersifat lokal). Karakteristik dan permasalahan ini juga ditemui di industri rumah tangga pembuatan onde-onde ubi ungu milik salah satu penduduk di Desa Kayangan, Kecamatan Diwek, Kabupaten Jombang. Tujuan kegiatan ini adalah: 1) meningkatkan produksi melalui bantuan berupa alat pengaduk dan peralatan proses produksi, 2) meningkatkan manajemen usaha melalui penyuluhan/pelatihan tentang pembukuan sederhana analisis biaya dan pendapatan, dan 3) memperluas wilayah pemasaran melalui penyuluhan/pelatihan tentang pemasaran online. Kegiatan yang dilaksanakan pada mitra adalah 1) memberikan bantuan alat pengaduk, beserta penyuluhan/pelatihan tentang pengoperasian dan perawatannya, 2) penyuluhan/pelatihan tentang pembukuan sederhana serta analisis biaya dan pendapatan, agar mitra dapat mengetahui keuntungan/kerugian usaha, 3) penyuluhan/pelatihan tentang teknik komunikasi pemasaran dan pemasaran online melalui Whatshapp, Facebook, Instagram Output yang dicapai adalah meningkatnya produksi sebesar 46%  dan pendapatan sebesar 45,8% serta ketrampilan mitra.